THE POSITION OF AJWIBAH AL FADHILAH LIL AS ILAH AL ASYARAH AL KAMILAH IN HADITH LITERATURE - Mahmud, Ihsan; Taufiq, Taufiq (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
This study conducts an analysis of the topic components encompassed within the literary composition entitled "Al Ajwibah Al Fadhilah Lil As Ilah Al 'Asyarah Al Kamilah." This research utilizes analytical and descriptive approaches in order to carry out a comprehensive literature assessment. The objective of this study is to evaluate the influence of the book on the discipline of hadith science through an analysis of its contribution in producing original issues. The book known as "Kitab Al Ajwibah Al Fadhilah Lil As Ilah Lil 'Asyarah Al Kamilah" is a noteworthy scholarly addition to the field of hadith discipline, emerging during a time characterized by restricted advancements in Islamic research. This literary work introduces original and unexplored issues that have not been previously examined in the existing body of scholarly literature pertaining to the field of hadith studies.